A high-strength, high-toughness, high-thermal-conductivity magnesium alloy and a processing method thereof
By using a formula with high content of Zn elements and multi-component alloying elements in magnesium alloys, combined with semi-solid thixotropic injection molding and heat treatment processes, the problem of existing magnesium alloys being unable to achieve both high thermal conductivity and high strength is solved, achieving high efficiency, Low-cost magnesium alloy finished products.
Patent Information
- Application Number
- CN202111457656.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-02
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-12-02
AI Technical Summary
Existing magnesium alloys cannot take into account both high thermal conductivity and high strength, and have high processing costs, making it difficult to meet the requirements of heat dissipation system materials in the fields of aerospace and transportation.
A magnesium alloy formula with a high content of Zn is used, combined with multi-element alloying of Ca, Mn, La, Ce, Si, Sb, Zr, Sn and other elements, and the mechanical properties of the magnesium alloy are improved through semi-solid thixoinjection molding technology and heat treatment process. performance and thermal conductivity.
The thermal conductivity of magnesium alloy is achieved ≥115W/(m·K), the yield strength is ≥200MPa, and the elongation is ≥8%. At the same time, the processing cost is reduced, and it is suitable for manufacturing heat dissipation/thermal conductive components with complex structures.
Smart Images

Figure BDA0003388355890000171 
Figure BDA0003388355890000181
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloy material forming, and in particular to a high-strength, high-toughness and high-thermal-conductivity magnesium alloy and a processing method thereof. Background Art
[0002] Magnesium is currently the lightest engineering structural material with a density of 1.738g / cm 3 , about 2 / 3 of aluminum and 1 / 4 of steel. In addition to the characteristics of structural materials, magnesium and magnesium alloys also have the characteristics of functional materials, such as high electromagnetic shielding efficiency, good damping performance and excellent thermal conductivity. Therefore, they are also considered to be the most promising lightweight materials in the fields of aerospace, rail transportation, automotive parts and 3C products.
[0003] The thermal conductivity of pure magnesium at room temperature is relatively high, about 154.5W / (m·K), and its thermal conductivity per unit mass is slightly better than that of aluminum. However, the yield strength of cast pure magnesium at room temperature is only 21MPa, which cannot be used as a structural part. Alloying is an effective way to improve the mechanical properties of magnesium alloys, but the addition of alloying elements will significantly reduce the thermal conductivity of magnesium alloys. For example, the commonly used die-cast magnesium alloys Mg-9Al-1Zn (AZ91) and Mg-6Al-0.5Mn (AM60), their thermal conductivity is less than 70W / (m·K), which is much lower than the thermal conductivity of pure magnesium.
[0004] At present, magnesium alloy heat dissipation / heat-conducting parts are basically made of the above-mentioned commercial magnesium alloys with low thermal conductivity, so they are increasingly unable to meet the requirements of high thermal conductivity products. The thermal conductivity of the commercial grade cast ZK61 magnesium alloy can reach 115W / (m·K), but the yield strength is usually lower than 180MPa, and it is difficult to meet the high strength, toughness and high thermal conductivity requirements for heat dissipation system structural materials in the field of aerospace devices and vehicles. Cast rare earth magnesium alloys have high thermal conductivity (thermal conductivity ≥115W / (m·K)) and mechanical properties (yield strength ≥180MPa), but rare earth magnesium alloys are relatively expensive, and the addition of a large amount of rare earth elements will significantly increase the density of magnesium alloys.
[0005] Literature reports that magnesium alloys with both high mechanical properties and high thermal conductivity can be prepared through deformation processes such as rolling, forging, and extrusion. However, the close-packed hexagonal crystal structure of magnesium alloys makes the deformation process complicated and costly. Especially when faced with magnesium alloy products with complex structures, the deformation process often cannot meet the requirements.
[0006] Semi-solid thixotropic injection molding uses the special easy-flowing characteristics of metal in semi-solid state for injection molding. The semi-solid phenomenon of metal, that is, the metal in the solid-liquid temperature zone only needs a very low shear stress to be stirred. At this time, the shear force is about three orders of magnitude lower than the shear force of the same liquid metal, which is easy to mold and has better mechanical properties than the traditional dendrite solidification casting method. It is particularly suitable for magnesium alloy molding.
[0007] Chinese patent CN109136699B discloses "high thermal conductivity magnesium alloy, inverter housing, inverter and automobile", and prepares Mg-Al-Zn-Mn-La-Ce-Nd-Sr-Cu cast magnesium alloy, whose chemical composition mass percentage is: Al: 2.0-4.0%, Mn: 0.1-0.3%, La: 1.0-2.0%, Ce: 2.0-4.0%, Nd: 0.1-1%, Zn: 0.5-2%, Ca: 0.1-0.5%, Sr: 0.1%, Cu≤0.1%, and the rest is Mg. The thermal conductivity of the alloy is greater than 110W / (m·K), but the yield strength is less than 160MPa and the elongation is 5%. Although it has a high thermal conductivity, the yield strength is low, which cannot meet the high strength, toughness and high thermal conductivity requirements for heat dissipation system structural materials in the field of aerospace devices and vehicles.
[0008] Chinese patent CN110819863B discloses "a low rare earth high thermal conductivity magnesium alloy and its preparation method", and prepares a Mg-Gd-Er-Zn-Zr cast magnesium alloy, whose chemical composition mass percentage is: Gd: 5.0-7.0%, Er: 0.5-2%, Zn: 3.0-7.0%, Zr: 0.5.-1.0%, and the rest is Mg. The thermal conductivity of the alloy is greater than 115W / (m·K), the yield strength is 200MPa, and the elongation is greater than 20%. However, a large amount of expensive rare earth elements Gd and Er are added to the alloy, resulting in a very high alloy cost.
[0009] Chinese patent CN104152769B discloses "a thermally conductive magnesium alloy and its preparation method", and prepares a Mg-Zn-Mn-Ce deformable magnesium alloy, whose chemical composition mass percentage is: Zn: 0.8-3.0%, Mn: 0.25-0.48%, Ce: 0.05-1.0%, impurity mass fraction ≤0.15%, and the rest is Mg. The deformation method is extrusion, rolling or forging. The thermal conductivity of the alloy is greater than 130W / (m·K), the yield strength is greater than 200MPa, and the elongation is greater than 20%. However, the alloy has a low content of Zn and other elements and its mechanical strength is not high enough. It can only be manufactured using a complex deformation processing process, and is not suitable for using the alloy to prepare products with complex structures.
[0010] In the prior art, the public document "Study on the Organization and Process of Semi-solid Thixotropic Injection of AZ91D Magnesium Alloy" prepared a Mg-Al-Zn semi-solid thixotropic injection molding alloy, whose chemical composition is 8.3% Al by mass, 0.54% Zn by mass, 0.14% Mn by mass, and the rest is Mg. The thermal conductivity of the alloy is less than 60W / (m·K), the yield strength is not mentioned, and the elongation is about 8%. The alloy cannot take into account both excellent mechanical properties and thermal conductivity at the same time, and its application field is limited.
[0011] In recent years, the miniaturization and integration of electronic devices have become a development trend, which puts higher and higher requirements on the thermal conductivity and mechanical properties of heat dissipation / heat conduction components to ensure that the products have high working stability and service life. Especially for complex structural parts of heat dissipation / heat conduction systems such as aerospace electronic devices, 3C products and transportation vehicles, which have urgent needs for lightweighting, it is necessary to ensure high thermal conductivity, excellent mechanical properties and low production costs. However, the current commercial magnesium alloys and magnesium alloy materials reported at home and abroad cannot take into account thermal conductivity, mechanical properties and processing costs at the same time. Therefore, it is urgent to carry out research on new magnesium alloy composition design and new forming technology to develop new high-strength, high-toughness and high-thermal conductivity magnesium alloys. Summary of the invention
[0012] The purpose of the present invention is to provide a high-strength, high-toughness and high-thermal-conductivity magnesium alloy and a processing method thereof, without adding expensive rare earth elements, using a low-cost alloy formula to solve the problem that the existing magnesium alloy cannot simultaneously take into account high thermal conductivity and high strength. The thermal conductivity of the magnesium alloy is ≥115W / (m·K), the yield strength is ≥200MPa, and the elongation is ≥8%; at the same time, the present invention adopts semi-solid thixotropic injection molding technology for processing, and its mechanical properties are close to those of deformed magnesium alloys, but its process is less difficult than the traditional plastic deformation method, low cost, easy to mass-produce, and can produce magnesium alloy products with complex structures that cannot be produced by deformation processes, which can be widely used in the preparation of heat dissipation / thermal conductive components in the fields of aerospace, 3C products, and automotive parts.
[0013] To achieve the above object, the technical solution of the present invention is:
[0014] A high-strength, toughness and high-thermal conductivity magnesium alloy, the components of which are as follows by weight: Zn: 8.0-12.0%, one or two of Ca or Mn, Ca≤2.0%, Mn≤2.0%, and one or more of La, Ce, Si, Sb, Zr and Sn, wherein La≤2.0%, Ce≤2.0%, Si≤2.5%, Sb≤2.0%, Zr≤1.0%, Sn≤2.0%, and the rest are Mg and unavoidable impurities.
[0015] The magnesium alloy of the present invention has a thermal conductivity of ≥115 W / (m·K), a yield strength of ≥200 MPa, and an elongation of ≥8%.
[0016] Research has found that the mechanical properties and thermal conductivity of magnesium alloys are closely related to the alloy composition and microstructure. Mechanisms that improve mechanical properties, such as solid solution strengthening, dispersion strengthening, dislocation strengthening, and grain refinement strengthening, often reduce their thermal conductivity.
[0017] The design idea of the present invention is to improve the mechanical properties of the material through the second phase strengthening mechanism, while minimizing the negative impact of the added alloy elements on the thermal conductivity of the material. This requires controlling the type and content of the alloy elements so that the material has both high strength and high thermal conductivity.
[0018] Among them, Zn can significantly improve the mechanical properties of magnesium alloys while having little negative impact on thermal conductivity; trace amounts of Mn, Ca, La, Ce, Si, Sb, Zr, and Sn elements can improve the mechanical properties of magnesium alloys by refining grains or forming a second phase strengthening without significantly reducing thermal conductivity.
[0019] The solid solubility of Zn element in Mg is about 6.2%, and Mg-Zn alloy has a wide solid-liquid two-phase region. Zn element and Mg form a series of Mg-Zn binary phases, which have solid solution strengthening and precipitation strengthening effects. Zn is also a weak grain refiner, which can obtain a finer microstructure, thereby improving the mechanical properties of magnesium alloys. The negative impact of Zn element on the thermal conductivity of magnesium alloys is much lower than that of Al element. Therefore, the thermal conductivity of Mg-Zn alloy is significantly better than that of Mg-Al alloy. If the Zn element content is too low, the fluidity of the semi-solid slurry is not good and cannot be fully filled; adding too much Zn element will affect the fluidity of the alloy, increase the tendency of microstructure to thermal cracking, and also reduce the thermal conductivity of the alloy. Therefore, the percentage of Zn element in the present invention is 8-12%.
[0020] The Mn element can refine the microstructure of the magnesium alloy and improve the corrosion resistance by controlling the Fe content. The appropriate amount of Mn content has a small negative impact on the thermal conductivity of the magnesium alloy, so the percentage of the Mn element in the present invention does not exceed 2%.
[0021] The Ca element has the effect of grain refinement in magnesium alloys, and can also inhibit the oxidation of magnesium alloy melts and improve the flame retardant properties of magnesium alloys. This element forms a second phase with a high melting point with Mg, which has a significant effect on improving the mechanical properties of the alloy. An appropriate amount of Ca element will not significantly reduce the thermal conductivity of magnesium alloys, so low alloying is adopted, and the mass percentage does not exceed 2%.
[0022] Rare earth elements La and Ce can refine the microstructure of magnesium alloys, purify alloy melts, improve alloy fluidity, and reduce alloy thermal tendency. Rare earth second phase particles can significantly improve the mechanical properties and heat resistance of magnesium alloys. Adding a small amount of La and Ce to magnesium alloys can make magnesium alloys have both excellent thermal conductivity and mechanical properties. Studies have shown that La and Ce have little negative impact on the thermal conductivity of magnesium alloys and are cheap rare earths. Therefore, the mass percentage of La and Ce in the present invention does not exceed 2%.
[0023] Si can improve the fluidity of the melt in the magnesium alloy, and the Mg2Si second phase formed during the solidification process is a very effective mechanical property strengthening phase to improve the mechanical properties of the magnesium alloy. However, the Si element will reduce the corrosion resistance of the magnesium alloy, so the mass percentage of Si in the present invention does not exceed 2.5%.
[0024] The solid solubility of Sb in the magnesium matrix is extremely small, and it mainly exists in the form of the second phase Mg3Sb2. Therefore, this element has little effect on the thermal conductivity of the magnesium alloy, and can improve the mechanical properties at room temperature. At the same time, Sb can also improve the casting properties of the Mg-Zn alloy. When the addition amount of Sb is greater than 2%, a large amount of continuous network second phase precipitates, which reduces the mechanical properties of the magnesium alloy. Therefore, the mass percentage of Sb in the present invention is 0-2%.
[0025] Zr is a strong grain refining element in magnesium alloys, especially as a good grain refining agent for Mg-Zn alloys. Zr has a very low solid solubility in Mg, and a small amount of addition will not have a significant effect on the thermal conductivity of magnesium alloys. Therefore, the mass percentage of Zr in the present invention does not exceed 1%.
[0026] Sn element forms a strengthening phase with Mg and Zn, which improves the mechanical properties of magnesium alloy while having little effect on thermal conductivity. The mass percentage of Sn in the present invention does not exceed 2%.
[0027] Semi-solid thixotropic injection molding alloys generally have a wide solid-liquid two-phase region. The semi-solid slurry of the alloy must have sufficient fluidity to fill the complex mold cavity, and at the same time ensure close to laminar filling without involving more gas. Therefore, the high-strength, toughness and high-thermal conductivity magnesium alloy of the present invention must be able to use the semi-solid thixotropic injection molding process, and it is also necessary to add alloying elements that are conducive to obtaining these characteristics to the magnesium alloy. In the present invention, a relatively high content of Zn element is added. When the Zn content is controlled at 8-12%, the fluidity of the semi-solid slurry is better and the mold can be completely filled; Ca, Zr, Mn, Si, Sb, Sn, La, Ce and other elements are selected for multi-element alloying. These elements have a small negative impact on the thermal conductivity of the magnesium alloy on the basis of improving the mechanical properties of the magnesium alloy. The content of each added element is controlled as much as possible below the solid solubility of each element, so that the high strength, toughness and high thermal conductivity of the alloy can be taken into account. The semi-solid slurry can also have better fluidity, and the semi-solid thixotropic injection molding process can be used to manufacture magnesium alloy products with complex structures that cannot be manufactured by deformation processes.
[0028] The processing method of the high-strength, high-toughness and high-thermal-conductivity magnesium alloy of the present invention comprises the following steps:
[0029] 1) Ingredients
[0030] Using pure Mg ingots, pure Zn ingots, pure Sb ingots, pure Sn ingots, Mg-Mn, Mg-Ca, Mg-La, Mg-Ce, Mg-Si and Mg-Zr master alloys as raw materials, and preparing the ingredients according to the weight percentage of the above magnesium alloy components;
[0031] 2) Melting
[0032] Putting a pure Mg ingot into a crucible of a smelting furnace, heating it to 700-720°C, completely melting it under the protection of a mixed protective gas of CO2 and SF6, then heating it to 750-770°C, sequentially adding a pure Zn ingot, a pure Sb ingot, a pure Sn ingot, one or more of Mg-Mn, Mg-Ca, Mg-La, Mg-Ce, Mg-Si and Mg-Zr master alloys into the melted melt, stirring it fully for 10-15 minutes after the alloy is completely melted, then adding a magnesium alloy flux and refining it for 15-20 minutes, removing the surface scum, and finally keeping it at 720-760°C for 20-30 minutes to cast it into a magnesium alloy ingot;
[0033] 3) Magnesium alloy particle processing
[0034] placing the magnesium alloy ingot in a granulator to process it into magnesium alloy particles;
[0035] 4) Semi-solid thixotropic injection molding
[0036] The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 550-630°C to form a semi-solid slurry of the magnesium alloy. A screw shearing device is used to apply a shearing force to the semi-solid slurry, and the screw speed is controlled at 100-180 r / min. After the shearing is completed, the semi-solid slurry of the magnesium alloy is injected into a mold to form a semi-solid metal part, and the injection speed is 2-5 m / s; the mold temperature is 200-300°C;
[0037] 5) Heat treatment
[0038] The obtained semi-solid metal parts are sequentially subjected to solution treatment and aging treatment, the solution treatment temperature is 300-450°C, and the insulation time is 1-36h; the aging treatment temperature is 150-200°C, and the insulation time is 4-168h.
[0039] Preferably, in step 2), the magnesium alloy flux is RJ-4 flux, RJ-5 flux or RJ-6 flux, preferably RJ-5 flux.
[0040] Preferably, in step 3), the size of the magnesium alloy particles is (1-2 mm)×(1-2 mm)×(4-6 mm).
[0041] Preferably, in step 4), the solid phase ratio of the semi-solid slurry is controlled within a range of 10 to 50% by volume.
[0042] In the semi-solid thixotropic injection molding process of the present invention, the barrel temperature is set at 550-630°C to achieve a semi-solid slurry solid phase ratio that meets the semi-solid thixotropic injection molding process. The solid phase ratio of the semi-solid slurry is controlled at 10-50% by volume, so that the material has higher strength and thermal conductivity. The injection speed is 2-5m / s. If the injection speed is too low, the material cannot be fully filled. If the injection speed is too high, the material porosity is high, and the mechanical properties and thermal conductivity will be reduced. In addition, for the alloy design in the present invention, the mold temperature is set at 200-300°C to prevent thermal cracking, achieve complete filling, and manufacture qualified magnesium alloy products.
[0043] The present invention adds a heat treatment process after semi-solid thixotropic injection molding to further improve the strength and toughness of the magnesium alloy and other excellent properties. After semi-solid thixotropic injection molding, the material has a small porosity and fine grains, but still has a coarse second phase. After heat treatment, a smaller second phase is precipitated, which increases the strengthening effect of the second phase and improves the mechanical properties of the material. In addition, after heat treatment, it is ensured that the alloy elements are completely dissolved in the magnesium matrix and a fine second phase is precipitated, which reduces the negative impact of the alloy elements on the thermal conductivity of the magnesium alloy and improves the thermal conductivity. Therefore, a heat treatment process is added after semi-solid thixotropic injection molding, and the mechanical properties and thermal conductivity of the material are improved at the same time by using solid solution strengthening and aging strengthening.
[0044] The solution treatment temperature of the present invention is 300-450°C, and the holding time is 1-36h, the purpose is to ensure that the alloy elements Zn, Si, Sb, Sn, Ca, La, Ce, and Zr are completely dissolved into the magnesium matrix as much as possible, and the grain size is controlled not to grow significantly. The aging treatment temperature is 150-200°C, and the holding time is 4-168h. The aging treatment temperature and time ensure the precipitation of fine second phases such as Mg-Zn, Mg-Si, Mg-Sb, Mg-Sn, Mg-Ca and other binary strengthening phases, as well as Mg-Zn-La, Mg-Zn-Ce, Mg-Zn-Ca and other ternary strengthening phases.
[0045] After the magnesium alloy is subjected to semi-solid treatment, it is subjected to heat treatment. Through solution treatment and aging treatment, a fine dispersed second phase can be precipitated, which significantly improves the mechanical properties of the material; the alloy of the present invention precipitates binary strengthening phases such as Mg-Zn, Mg-Si, Mg-Sb, Mg-Sn, Mg-Ca, and ternary strengthening phases such as Mg-Zn-La, Mg-Zn-Ce, Mg-Zn-Ca after heat treatment, which improves the mechanical properties of the material; at the same time, through solution treatment and aging treatment, the degree of lattice distortion is reduced, and the thermal conductivity of the material is improved. Therefore, the heat treatment method of solution treatment + aging treatment can simultaneously improve the mechanical properties and thermal conductivity of the material.
[0046] Traditional die-cast magnesium alloys are cast using a die-casting process. Regardless of the composition, a high porosity will be generated inside the magnesium alloy, thereby reducing the mechanical properties and thermal conductivity of the magnesium alloy. And due to the high porosity inside the magnesium alloy, it is impossible to improve the mechanical properties and thermal conductivity of the material through subsequent heat treatment.
[0047] Traditional deformed magnesium alloys use deformation processes, which can make magnesium alloys obtain excellent thermal conductivity and mechanical properties. Deformation processes such as extrusion, forging, rolling, etc. However, the magnesium alloy has a close-packed hexagonal crystal structure inside, which makes the process more complicated and costly when using deformation processes to manufacture magnesium alloy products, and it is impossible to produce magnesium alloy products with complex structures.
[0048] The present invention adopts a semi-solid thixotropic injection molding + heat treatment process, combined with the composition control of the magnesium alloy of the present invention, to effectively balance the mechanical properties and thermal conductivity of the magnesium alloy, ensuring that the magnesium alloy material has both high strength and toughness and high thermal conductivity.
[0049] Beneficial effects of the present invention:
[0050] 1. The high-strength, toughness and high-thermal-conductivity magnesium alloy of the present invention is composed of conventional alloying elements Zn, Ca and / or Mn as basic elements, and a small amount of La, Ce, Si, Sb, Zr and Sn elements are added to improve the mechanical properties of the material through the second phase strengthening mechanism. At the same time, the addition amount of La, Ce, Si, Sb, Zr and Sn elements is controlled to minimize the negative impact of the added alloying elements on the thermal conductivity of the material. Without adding any expensive rare earth elements, the obtained magnesium alloy has both high thermal conductivity and high strength properties. The thermal conductivity of the magnesium alloy is ≥115W / (m·K), the yield strength is ≥200MPa and the elongation is ≥8%.
[0051] 2. The present invention adopts a relatively high content of Zn element in the composition design, and selectively adds elements such as Ca, Zr, Mn, Si, Sb, Sn, La, and Ce for multi-element alloying, and controls the content of each added element to be below its respective solid solubility. On the basis of ensuring that the magnesium alloy has high mechanical properties and thermal conductivity, the semi-solid slurry of the alloy is controlled to have sufficient fluidity, and a semi-solid thixotropic injection molding process can be used for molding to fill complex mold cavities, ensuring near-laminar filling without involving much gas, and manufacturing magnesium alloy products with complex structures that cannot be manufactured by deformation processes. The magnesium alloy products can be used to manufacture complex structural parts of heat dissipation / heat conduction systems such as aerospace electronic devices, 3C products, and transportation vehicles.
[0052] 3. The present invention adopts semi-solid thixotropic injection molding technology, and achieves complete filling by controlling the heating temperature, injection speed and mold temperature to produce qualified magnesium alloy products; after semi-solid thixotropic injection molding, a heat treatment process is added, and solid solution strengthening and aging strengthening are used to further improve the mechanical properties and thermal conductivity of the magnesium alloy. The mechanical properties of the magnesium alloy obtained are close to those of the deformed magnesium alloy, but it has higher thermal conductivity, and the process is less difficult than the traditional solid plastic deformation method, low cost, and easy to mass produce. At the same time, it can produce magnesium alloy products with complex structures that cannot be produced by deformation processes. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is described in detail below through examples. This example is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following examples.
[0054] The magnesium alloy composition of the embodiment of the present invention is shown in Table 1, and the rest is Mg and inevitable impurities.
[0055] Example 1
[0056] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 10.3wt% Zn, 0.3wt% Mn, 1.5wt% Ca, 0.5wt% La, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Mn, Mg-Ca, and Mg-La master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0057] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 713℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 750℃, add the pure Zn ingot, Mg-Mn, Mg-Ca, and Mg-La master alloys into the melt in sequence, stir it for 12min after the alloy is completely melted, add RJ-5 flux and refine it for 20min, remove the surface scum, and finally keep it at 730℃ for 20min to cast it into a magnesium alloy ingot;
[0058] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles with a size of 1 mm×1 mm×5 mm;
[0059] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 580° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 130 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 3 m / s. The mold temperature is 240° C.
[0060] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 320° C. and the holding time is 8 h; the aging treatment temperature is 170° C. and the holding time is 120 h.
[0061] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0062] Example 2
[0063] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 11.2wt% Zn, 0.5wt% Ca, 0.1wt% La, 0.8wt% Ce, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Ca, Mg-La, and Mg-Ce master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0064] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 700℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, Mg-Ca, Mg-La, and Mg-Ce master alloys into the melt in sequence, stir it for 10min after the alloy is completely melted, add RJ-4 flux and refine it for 19min, remove the surface scum, and finally keep it at 720℃ for 20min to cast it into a magnesium alloy ingot;
[0065] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1 mm×1.5 mm×4 mm;
[0066] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 570°C to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry at a screw speed of 120 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part at an injection speed of 3.6 m / s. The mold temperature is 220°C.
[0067] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 335° C. and the holding time is 36 h; the aging treatment temperature is 180° C. and the holding time is 96 h.
[0068] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0069] Example 3
[0070] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 11.8wt% Zn, 0.1wt% Ca, 0.2wt% Ce, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Ca, and Mg-Ce master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0071] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 709℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, Mg-Ca, and Mg-Ce master alloy into the melt in sequence, stir it for 11min after the alloy is completely melted, add RJ-5 flux and refine it for 15min, remove the surface scum, and finally keep it at 735℃ for 20min to cast it into a magnesium alloy ingot;
[0072] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 2 mm×1.2 mm×5.5 mm;
[0073] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 590° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 150 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 3.8 m / s. The mold temperature is 230° C.
[0074] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 450° C. and the holding time is 1 h; the aging treatment temperature is 175° C. and the holding time is 75 h.
[0075] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0076] Example 4
[0077] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 8.3wt% Zn, 1.3wt% Ca, 0.6wt% Zr, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Ca, and Mg-Zr master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0078] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 713℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, Mg-Ca, and Mg-Zr master alloy into the melt in sequence, stir it for 10min after the alloy is completely melted, add RJ-5 flux and refine it for 16min, remove the surface scum, and finally keep it at 740℃ for 20min to cast it into a magnesium alloy ingot;
[0079] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.5 mm×1.5 mm×4 mm;
[0080] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 570°C to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry at a screw speed of 120 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part at an injection speed of 4 m / s. The mold temperature is 260°C.
[0081] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 350° C. and the holding time is 26 h; the aging treatment temperature is 160° C. and the holding time is 50 h.
[0082] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0083] Example 5
[0084] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 10.1wt% Zn, 1.5wt% Mn, 1.0wt% Sn, and the rest is Mg, and pure Mg ingots, pure Zn ingots, pure Sn ingots, and Mg-Mn master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0085] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 710℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 765℃, add the pure Zn ingot, Mg-Mn, Mg-Ca, and Mg-La master alloys into the melt in sequence, stir it thoroughly for 14 minutes after the alloy is completely melted, add RJ-5 flux and refine it for 18 minutes, remove the surface scum, and finally keep it at 740℃ for 20 minutes to cast it into a magnesium alloy ingot;
[0086] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.2 mm×2.0 mm×4.5 mm;
[0087] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 550° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 150 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 3.8 m / s. The mold temperature is 260° C.
[0088] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 340° C. and the holding time is 32 h; the aging treatment temperature is 150° C. and the holding time is 168 h.
[0089] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0090] Example 6
[0091] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 10.9wt% Zn, 2.0wt% Ca, 1.5wt% Si, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Ca, and Mg-Si master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0092] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 718℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, Mg-Ca, and Mg-Si master alloy into the melt in sequence, stir it for 11min after the alloy is completely melted, add RJ-6 flux and refine it for 20min, remove the surface scum, and finally keep it at 730℃ for 20min to cast it into a magnesium alloy ingot;
[0093] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.6 mm×1.8 mm×5.5 mm;
[0094] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 560° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 150 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 3 m / s. The mold temperature is 280° C.
[0095] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 325° C. and the holding time is 2 h; the aging treatment temperature is 190° C. and the holding time is 150 h.
[0096] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0097] Example 7
[0098] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 9.5wt% Zn, 2.0wt% Mn, 0.3wt% La, 0.8wt% Sb, and the rest is Mg, and pure Mg ingots, pure Zn ingots, pure Sb ingots, Mg-Mn, and Mg-La master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0099] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 715℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 755℃, add the pure Zn ingot, Mg-Mn, Mg-Ca, and Mg-La master alloys into the melt in sequence, stir it for 15min after the alloy is completely melted, add RJ-5 flux and refine it for 15min, remove the surface scum, and finally keep it at 730℃ for 20min to cast it into a magnesium alloy ingot;
[0100] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 2.0 mm×2.0 mm×4.5 mm;
[0101] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 570°C to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry at a screw speed of 160 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part at an injection speed of 2.8 m / s. The mold temperature is 210°C.
[0102] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 320° C. and the holding time is 36 h; the aging treatment temperature is 200° C. and the holding time is 4 h.
[0103] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0104] Example 8
[0105] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 8.0wt% Zn, 0.2wt% Mn, 1.2wt% Ca, 0.2wt% Ce, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Mn, Mg-Ca, and Mg-Ce master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0106] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 720℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, Mg-Mn, Mg-Ca, and Mg-Ce master alloys into the melt in sequence, stir it thoroughly for 10min after the alloy is completely melted, add RJ-5 flux and refine it for 16min, remove the surface scum, and finally keep it at 750℃ for 20min to cast it into a magnesium alloy ingot;
[0107] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.3 mm×1.9 mm×4.8 mm;
[0108] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 580° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 120 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 3 m / s. The mold temperature is 270° C.
[0109] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 300° C. and the holding time is 20 h; the aging treatment temperature is 185° C. and the holding time is 120 h.
[0110] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0111] Example 9
[0112] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 11.3wt% Zn, 1.1wt% Mn, 1.3wt% Ce, 0.5wt% Sb, and the rest is Mg, and pure Mg ingots, pure Zn ingots, pure Sb ingots, Mg-Mn, and Mg-Ce master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0113] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 705℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 760℃, add the pure Zn ingot, pure Sb ingot, Mg-Mn, and Mg-Ce master alloy into the melt in sequence, and after the alloy is completely melted, stir it for 13min, then add RJ-5 flux and refine it for 19min, remove the surface scum, and finally keep it at 720℃ for 20min to cast it into a magnesium alloy ingot;
[0114] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.4 mm×1.3 mm×5.2 mm;
[0115] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 570°C to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry at a screw speed of 150 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part at an injection speed of 2.8 m / s. The mold temperature is 220°C.
[0116] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 315° C. and the holding time is 28 h; the aging treatment temperature is 200° C. and the holding time is 40 h.
[0117] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0118] Example 10
[0119] 1) The composition content of the high plasticity and thermal conductivity magnesium alloy is designed to be: 12.0wt% Zn, 0.3wt% Ca, 0.9wt% La, and the rest is Mg, and pure Mg ingots, pure Zn ingots, Mg-Ca, and Mg-La master alloys are used as raw materials, and the ingredients are prepared according to the weight percentage of the magnesium alloy components designed;
[0120] 2) Put the pure Mg ingot into the crucible of the melting furnace, heat it to 700℃, and completely melt it under the protection of the mixed protective gas of CO2 and SF6, then heat it to 770℃, add the pure Zn ingot, Mg-Ca, and Mg-La master alloy into the melt in sequence, stir it for 10min after the alloy is completely melted, add RJ-5 flux and refine it for 15min, remove the surface scum, and finally keep it at 760℃ for 20min to cast it into a magnesium alloy ingot;
[0121] 3) placing the magnesium alloy ingot in a granulator to produce magnesium alloy particles having a size of 1.7 mm×1.6 mm×4.4 mm;
[0122] 4) The magnesium alloy particles are placed in the barrel of a semi-solid thixotropic injection molding device and heated to 580° C. to form a semi-solid slurry. A screw shearing device is used to apply shear force to the semi-solid slurry. The screw speed is 120 r / min. After the shearing is completed, the magnesium alloy semi-solid slurry is injected into a mold to form a semi-solid part. The injection speed is 2.5 m / s. The mold temperature is 210° C.
[0123] 5) The semi-solid magnesium alloy parts are subjected to solution treatment and aging treatment in sequence; the solution treatment temperature is 410° C. and the holding time is 4 h; the aging treatment temperature is 190° C. and the holding time is 60 h.
[0124] The properties of the obtained magnesium alloy parts are shown in Table 2.
[0125] Comparative Example 1
[0126] The percentage content of the selected magnesium alloy components is: 9wt% Al, 1wt% Zn, and the rest is Mg.
[0127] Pure Mg ingot, pure Al ingot and pure Zn ingot are used as raw materials, and the alloy ratio is designed according to the mass percentage of the above elements. Pure Mg ingot is added to a crucible furnace protected by CO2+SF6 gas, and the temperature is raised to 720℃ until it is completely melted. After the temperature is raised to 760℃, pure Al ingot and pure Zn ingot are added in sequence. After the alloy is completely melted, it is fully stirred for 10 minutes, and then RJ-5 flux is added for refining for 15 minutes, and the surface scum is removed. It is kept at 720-760℃ and kept still for 20 minutes, and then transferred to the heat preservation furnace of the die casting machine; die casting is carried out on the magnesium alloy die casting machine, and the melt temperature is 650℃ and the mold temperature is 250℃ to obtain AZ91D die castings.
[0128] Its thermal conductivity and mechanical properties are shown in Table 2: the alloy has a thermal conductivity of 55 W / (m·K), a tensile strength of 256 MPa, a yield strength of 150 MPa, and an elongation of 4.5%.
[0129] Comparative Example 2
[0130] The percentage content of the selected magnesium alloy components is: 6wt% Al, 0.5wt% Mn, and the rest is Mg.
[0131] Pure Mg ingot, pure Al ingot and Mg-Mn master alloy are used as raw materials, and the alloy ratio is designed according to the mass percentage of the above elements. Add pure Mg ingot to the crucible furnace protected by CO2+SF6 gas, heat it to 720℃ and wait for it to be completely melted, then increase the temperature to 760℃ and add pure Al ingot and Mg-Mn master alloy in turn, wait until the alloy is completely melted and stir it for 10 minutes, then add RJ-5 and refine it for 15 minutes, remove the surface scum, keep it at 720-760℃ and let it stand for 20 minutes, and finally cast it into magnesium alloy ingot. Transfer it to the heat preservation furnace of the die casting machine; die-cast it on the magnesium alloy die casting machine, and obtain AM60B die casting with a melt temperature of 660℃ and a mold temperature of 250℃.
[0132] Its thermal conductivity and mechanical properties are shown in Table 1: the alloy has a thermal conductivity of 63 W / (m·K), a tensile strength of 230 MPa, a yield strength of 132 MPa, and an elongation of 12%.
[0133] As can be seen from Table 2, the magnesium alloy obtained in the present invention has significantly improved yield strength and tensile strength, and the thermal conductivity is also significantly improved compared with the traditional AZ91D magnesium alloy and AM60B magnesium alloy. The thermal conductivity of the magnesium alloy of the present invention is ≥115W / (m·K), while the thermal conductivity of the traditional AZ91D magnesium alloy and AM60B magnesium alloy is only about 60W / (m·K).
[0134]
[0135]
Claims
1. A high-strength, high-toughness and high-thermal-conductivity magnesium alloy, the composition weight percentage of which is: Zn: 8.0-12.0%, one or two of Ca or Mn, Ca: 1.2-2.0%, Mn: 1.1-2.0%, and also includes one or more of Si, Sb, Zr, Sn, wherein: Si≤2.5%, Sb≤2.0%, Zr≤1.0%, Sn≤2.0%, and the rest is Mg and unavoidable impurities; the specific preparation comprises the following steps: 1) Ingredients Using pure Mg ingots, pure Zn ingots, pure Sb ingots, pure Sn ingots, Mg-Mn, Mg-Ca, Mg-Si and Mg-Zr master alloys as raw materials, the ingredients are prepared according to the weight percentage of the above magnesium alloy components; 2) Melting Putting a pure Mg ingot into a crucible of a melting furnace, heating it to 700-720°C, completely melting it under the protection of a mixed protective gas of CO2 and SF6, then heating it to 750-770°C, sequentially adding a pure Zn ingot, a pure Sb ingot, a pure Sn ingot, one or more of Mg-Mn, Mg-Ca, Mg-Si and Mg-Zr master alloys into the melted melt, stirring it fully for 10-15 minutes after the alloy is completely melted, then adding a magnesium alloy flux and refining it for 15-20 minutes, removing the surface scum, and finally keeping it at 720-760°C for 20-30 minutes to cast it into a magnesium alloy ingot; 3) Magnesium alloy particle processing Placing the magnesium alloy ingot in a granulator to process it into magnesium alloy particles, wherein the size of the magnesium alloy particles is (1-2 mm)×(1-2 mm)×(4-6 mm); 4) Semi-solid thixotropic injection molding The magnesium alloy particles are placed in a barrel of a semi-solid thixotropic injection molding device and heated to 550-630° C. to form a semi-solid slurry of the magnesium alloy, and a screw shearing device is used to apply a shearing force to the semi-solid slurry, and the screw speed is controlled at 100-180 r / min; after the shearing is completed, the semi-solid slurry of the magnesium alloy is injected into a mold to form a semi-solid metal part, and the injection speed is 2-5 m / s; the mold temperature is 200-300° C.; the solid phase ratio of the semi-solid slurry is controlled to be 10-50% by volume; 5) Heat treatment The obtained semi-solid metal parts are sequentially subjected to solution treatment and aging treatment, the solution treatment temperature is 300-450°C, and the insulation time is 1-36h; the aging treatment temperature is 150-200°C, and the insulation time is 4-168h.
2. The high-strength, toughness and high-thermal conductivity magnesium alloy according to claim 1, characterized in that: The magnesium alloy has a thermal conductivity of ≥115 W / (m·K), a yield strength of ≥200 MPa, and an elongation of ≥8%.
3. The method for processing a high-strength, high-toughness and high-thermal-conductivity magnesium alloy according to claim 1 or 2, characterized in that: The following steps are involved: 1) Ingredients Pure Mg ingots, pure Zn ingots, pure Sb ingots, pure Sn ingots, Mg-Mn, Mg-Ca, Mg-Si and Mg-Zr master alloys are used as raw materials and the ingredients are prepared according to the weight percentage of the magnesium alloy components described in claim 1; 2) Melting Putting a pure Mg ingot into a crucible of a melting furnace, heating it to 700-720°C, completely melting it under the protection of a mixed protective gas of CO2 and SF6, then heating it to 750-770°C, sequentially adding a pure Zn ingot, a pure Sb ingot, a pure Sn ingot, one or more of Mg-Mn, Mg-Ca, Mg-Si and Mg-Zr master alloys into the melted melt, stirring it fully for 10-15 minutes after the alloy is completely melted, then adding a magnesium alloy flux and refining it for 15-20 minutes, removing the surface scum, and finally keeping it at 720-760°C for 20-30 minutes to cast it into a magnesium alloy ingot; 3) Magnesium alloy particle processing Placing the magnesium alloy ingot in a granulator to process it into magnesium alloy particles, wherein the size of the magnesium alloy particles is (1-2 mm)×(1-2 mm)×(4-6 mm); 4) Semi-solid thixotropic injection molding The magnesium alloy particles are placed in a barrel of a semi-solid thixotropic injection molding device and heated to 550-630° C. to form a semi-solid slurry of the magnesium alloy, and a screw shearing device is used to apply a shearing force to the semi-solid slurry, and the screw speed is controlled at 100-180 r / min; after the shearing is completed, the semi-solid slurry of the magnesium alloy is injected into a mold to form a semi-solid metal part, and the injection speed is 2-5 m / s; the mold temperature is 200-300° C.; the solid phase ratio of the semi-solid slurry is controlled to be 10-50% by volume; 5) Heat treatment The obtained semi-solid metal parts are sequentially subjected to solution treatment and aging treatment, the solution treatment temperature is 300-450°C, and the insulation time is 1-36h; the aging treatment temperature is 150-200°C, and the insulation time is 4-168h.
4. The method for processing a high-strength, high-toughness and high-thermal-conductivity magnesium alloy as claimed in claim 3, characterized in that: In step 2), the magnesium alloy flux is RJ-4 flux, RJ-5 flux or RJ-6 flux.
Citation Information
Patent Citations
A kind of thermal conductivity magnesium alloy and preparation method thereof
CN104152769B
High thermal conductivity magnesium alloys, inverter housings, inverters and automobiles
CN109136699B
A low-rare-earth, high-thermal-conductivity magnesium alloy and its preparation method
CN110819863B
High-thermal-conductivity die-casting magnesium alloy and preparation technology thereof
CN105779838A
Method for preparing graphene reinforced magnesium matrix composite material by injection moulding
CN108746628A